2002
DOI: 10.1128/jb.184.19.5223-5233.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of Flagellins FlaA and FlaB3 within Flagella ofMethanococcus voltae

Abstract: While they are functionally similar, archaeal flagella have characteristics not typically seen in bacterial flagella (37). Archaeal flagellins are synthesized with a leader peptide (3, 18), which is cleaved prior to the incorporation of the flagellin into the filament, similar to the processing of type IV pilins before incorporation into the pilus (34). A Methanococcus maripaludis protein (FlaK) possessing preflagellin peptidase activity has recently been reported (2). Archaeal flagellins show sequence similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…Two peptides for FlaA (13%) were also observed, including one glycopeptide (see Supplemental Table 1). These results are consistent with the fact that FlaA is the least abundant of the four flagellin components of the flagellar filament (6). In addition, FlaA may be resistant to enzymatic digestion as a consequence of its location within the flagellar filament.…”
Section: Nano-lc-ms/ms Analysis Of Flagellin Peptidesupporting
confidence: 79%
See 2 more Smart Citations
“…Two peptides for FlaA (13%) were also observed, including one glycopeptide (see Supplemental Table 1). These results are consistent with the fact that FlaA is the least abundant of the four flagellin components of the flagellar filament (6). In addition, FlaA may be resistant to enzymatic digestion as a consequence of its location within the flagellar filament.…”
Section: Nano-lc-ms/ms Analysis Of Flagellin Peptidesupporting
confidence: 79%
“…To improve the coverage of the less abundant proteins the same analyses were carried out on intact flagellin preparations that retained a partial anchoring structure. It has been demonstrated previously that the FlaB3 protein is enriched in these preparations (6). Improved coverage was obtained for FlaB1 (77%), FlaB2 (98%), and FlaB3 (71%).…”
Section: Nano-lc-ms/ms Analysis Of Flagellin Peptidementioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the relative content of archaellin B2 in the H. salinarum archaella is much higher than that of the hook-forming archaellin B3 in Methanococcus voltae. In the latter case, B3 is present in an amount hardly detected by electrophoresis of native archaella [11], while the share of H. salinarum archaellin B2 in wildtype archaella is about 15% that is apparently in excess for hook formation. It is possible that the presence of archaellin B2 along the whole length of the filament can someway stabilize the archaella helical structure [8].…”
Section: Resultsmentioning
confidence: 97%
“…Most studies on the role of multiple archaellins used methods of inactivation and deletion of genes [3]. Jarrell and co-workers have identified and localized minor archaellins FlaA1 and FlaB3 in the Methanococcus voltae filament, using antibodies specific to the variable regions of archaellins, and showed that FlaA1 is distributed over the entire length of the filament, while FlaB3 forms a short curved hook proximal to the cell [11].…”
Section: Introductionmentioning
confidence: 99%